The Effect of Brand, Product Completeness and Product Quality on Consumer Satisfaction and Its Impact on Repeat Orders at Srala Store - Arfiana, Syarifah Risna; Mahdani,; Kesuma, T. Meldi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to determine the effect of brand, product variety, and product quality on repeat order decisions through the mediation role of consumer satisfaction at the Srala.id Store in Banda Aceh. The approach used is path analysis with primary data collected through a survey conducted on consumers of the Srala.id Store. Respondents in this study were all consumers who had made repeat orders at the Srala Store in Banda Aceh City, totaling 300 people. Data were analyzed using SEM AMOS. The results of the analysis show that brand, product variety, and product quality have a positive and significant effect on consumer satisfaction. Furthermore, consumer satisfaction also shows a positive and significant relationship with repeat order decisions. In addition, this study identifies the indirect effect of brand, product variety, and product quality on repeat order decisions, which are mediated by consumer satisfaction, highlighting the importance of this mediating variable. These findings suggest that efforts to increase repeat order frequency can be achieved by strengthening the brand, ensuring product variety, and improving product quality, while maintaining consumer satisfaction at an optimal level. The practical implications of this research emphasize the need for continuous innovation and improvement in aspects that contribute to consumer experience, to maintain customer loyalty and support long-term sales growth.